Psychological morbidities amongst house officers in Kuching, Sarawak, Malaysia - Chia Minn, Yeoh (2015)
BACKGROUND: Psychological morbidities are common amongst healthcare professionals. This includes junior house officers who are just transitioning from being a medical student to a doctor. They undergo many stressors during this period and hence might suffer from higher psychological morbidities such as depression anxiety and stress. OBJECTIVE: The purpose of this study is to determine the prevalence of psychological morbidities such as Depression, Anxiety and Stress and their coping mechanisms in a population of house officers in Sarawak General Hospital, Kuching, Sarawak. The socio-demographic factors were also evaluated. METHOD: This is a cross-sectional study involving 227 house officers in Sarawak General Hospital, Kuching, Sarawak over a period of 3 months. The sociodemographic factors including age, sex, marital status, current posting, duration of posting, place of graduate and state of origin were evaluated. The DASS (depression, anxiety and stress scale) and CISS (coping inventory in stressful situations) were completed to assess the psychological morbidities and their corresponding coping mechanisms. RESULTS: The overall prevalence of depression, anxiety and stress amongst house officers in Sarawak General Hospital is high. The highest psychological morbidity noted is anxiety, which is 50% of the population, followed by stress 43% and depression 42%. There is no significant association between socio-demographic factors such as gender, marital status and state of origin with depression, anxiety and stress. However there is a significant association between local and foreign graduates whereby foreign graduates show a higher prevalence of depression, anxiety and stress (p<0.001). There is significant association between emotion oriented coping and depression, anxiety and stress (p<0.001). There is also significant association between task oriented coping and depression (p=0.04), distraction oriented coping and stress (p=0.02) and social diversion oriented coping and depression (p=0.03) CONCLUSION: There is a high prevalence of depression, anxiety and stress amongst house officers in Kuching, Sarawak with no association to the sociodemographic factors. However, there is a significant association between local and foreign graduates with the prevalence of DASS and higher prevalence of DASS is seen in emotion oriented coping.